Organizational Tie (De)activation During Crisis - Fitzhugh, Sean M.; DeCostanza, Arwen H. (Proceedings of the 2017 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining 2017, 2017)
Communication ties afford access to valuable information and resources, but obtaining these advantages requires the effort of forming and maintaining those ties. Preserving a balance between tie benefits and tie costs is essential for members of organizations that require coordination and continuous communication to execute complex tasks. Disrupted task environments exacerbate the challenge of maintaining this balance by 1) increasing the communication load necessary for efficient task execution and 2) increasing the cognitive load necessary for any one individual to carry out his/her duties. In this paper we examine email communication within a military organization performing multifaceted, interdependent tasks prior to and during a crisis event. Using a dynamic model of the evolving communication network, we assess how structural, individual, and tie-based attributes influence one's decision to preserve or dissolve outbound ties and either enhance or degrade an individual's appeal as a communication partner. We find evidence of outbound tie dissolution, particularly among those whose roles or knowledge suggest they would have important information to share, although we also find preservation of strategically valuable ties. The discrepancy between patterns of outbound and inbound tie dissolution suggests that active and passive ties may be subject to differential pressures towards preservation or dissolution.